2021
DOI: 10.1186/s12955-021-01756-2
|View full text |Cite
|
Sign up to set email alerts
|

The differences in health-related quality of life between younger and older adults and its associated factors in patients with type 2 diabetes mellitus in Indonesia

Abstract: Background It is well known that diabetes mellitus (DM) affects health-related quality of life (HRQOL) in both younger (aged 18–64 years) and older adults (aged ≥ 65 years). However, to date, no study has compared HRQOL and its predictors between younger and older adults with DM in Indonesia. Such a comparison is important because the results can guide nurses and clinicians to establish evidence-based educational programs that are specific and suitable for patients. Therefore, the aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
5
15
0
Order By: Relevance
“…Concerning QoL, the data showed that compared with older adults, young adults had significantly higher scores for QoL and some subscales including physical health and environment. Living alone, missing important people in life, lower physical and mental health, and less social and emotional support may be among the possible reasons for a lower QoL among older adults than younger adults [ 22 , 24 , 51 ]. Finally, we found that in young adults, PA (e.g., MPA, VPA, and MVPA) was correlated with QoL and all its subscales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning QoL, the data showed that compared with older adults, young adults had significantly higher scores for QoL and some subscales including physical health and environment. Living alone, missing important people in life, lower physical and mental health, and less social and emotional support may be among the possible reasons for a lower QoL among older adults than younger adults [ 22 , 24 , 51 ]. Finally, we found that in young adults, PA (e.g., MPA, VPA, and MVPA) was correlated with QoL and all its subscales.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that PA is a strong predictor of quality of life (QoL) [ 20 ]. QoL is a broad multidimensional concept that refers to an individual’s perception of their position in life and opportunities for happy and active participation in sociocultural, economic, and political life [ 21 , 22 ]. Improving the quality of life is widely regarded as a priority area of health interventions even if the economic status and social conditions of countries are not conducive to such actions [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 In patients with type 2 diabetes mellitus, older (aged ≥65 years) patients reported lower physical component summary scores of QOL than younger (aged <65 years). 9 As described above, older BCSs may have decreased muscle strength and muscle mass, and decreased balance function compared to middle-aged BCSs. QOL may also be reduced in older BCSs.…”
Section: Introductionmentioning
confidence: 94%
“…The scale was developed based on previous self-report instruments, resulting in four sub-dimensions with 17 items: five items for emotional burden, four items for physician distress, five items for regimen distress, and three items for interpersonal distress [ 18 , 19 ]. For each item, scores range from 1 to 6 (1 = not a problem , 2 = a slight problem , 3 = a moderate problem , 4 = a somewhat serious problem , 5 = a serious problem , or 6 = a very serious problem ) [ 20 ]. Each sub-scale was scored separately by averaging the total score of the sub-scale, while the total score is generated by averaging all item responses [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%